Baculovirus vectors in experimental geneand vaccine therapy - Solomko, A.P.; Zaharuk, O.A.; Chaschina, L.I.; Strokovskaya, L.I. (Вiopolymers and Cell, 2011)
The article provides a brief overview of the literature on target design, exploration properties and
effectiveness of the application of recombinant baculoviruses in model systems in vivo. The results of
experiments with wild and recombinant baculoviruses are analysed in regard to the priority areas of
biomedicine such as tissue regeneration, gene therapy of cancer, development of vaccines against
infe tious diseases and malignancies.
Keywords: baculovirus, gene- and immunovector, mammals, system in vivo. Представлен краткий обзор данных литературы по целевому конструированию и исследованию
свойств и эффективности применения в модельных системах in vivo рекомбинантных бакуловирусов.
Проанализированы результаты экспериментов с использованием диких и рекомбинантных бакуловирусов в таких приоритетных областях биомедицины, как регенерация тканей, генотерапия рака, разработка вакцин против инфекционных заболеваний и злокачественных новообразований.
Ключевые слова: бакуловирус, гено- и иммуновектор, млекопитающие, система in vivo. Представлено короткий огляд даних літератури стосовно цільового конструювання і дослідження властивостей та ефективності використано в модельних системах in vivo рекомбінантних
бакуловірусів. Проаналізовано результати дослідів із застосуванням диких і рекомбінантних бакуловірусів у таких пріоритетних галузях сучасної біомедицини, як регенерація тканин,
генотерапія раку, розробка вакцин проти інфекційних захворювань та злоякісних новоутворень.
Ключові слова: бакуловірус, гено- та імуновектор, ссавці, система in vivo.